2000
DOI: 10.1111/j.1469-7793.2000.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mechanisms involved in uterine contractions during pregnancy in guinea‐pigs

Abstract: The mechanisms involved in contraction in guinea‐pig myometrium were compared at mid‐ and late pregnancy. Tension was recorded simultaneously with either membrane potential or cytoplasmic calcium ([Ca2+]i) in strips exposed briefly to prostaglandin F2α (PGF). PGF‐induced increases in tension were underpinned by action potentials followed by sustained depolarization and biphasic increases in [Ca2+]i at mid‐ (peak, 879 ± 199 nM; sustained, 298 ± 35 nM, n= 11) and late pregnancy (peak, 989 ± 302 nM; sustained 178… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 47 publications
4
24
0
Order By: Relevance
“…The results are consistent with a previous study that mibefradil inhibited the frequency as well as amplitude of uterine contractility (Asokan et al, 2002 ]i and force. According to the previous report, high K + -induced contraction is due to Ca 2+ influx through L-type Ca 2+ channel by membrane depolarization (Shmigol et al, 1998;Coleman et al, 2000). In the present study, we also showed that 1 μM nifedipine, L-type Ca 2+ channel blocker, completely inhibited high K + -induced contraction.…”
Section: Discussionsupporting
confidence: 69%
“…The results are consistent with a previous study that mibefradil inhibited the frequency as well as amplitude of uterine contractility (Asokan et al, 2002 ]i and force. According to the previous report, high K + -induced contraction is due to Ca 2+ influx through L-type Ca 2+ channel by membrane depolarization (Shmigol et al, 1998;Coleman et al, 2000). In the present study, we also showed that 1 μM nifedipine, L-type Ca 2+ channel blocker, completely inhibited high K + -induced contraction.…”
Section: Discussionsupporting
confidence: 69%
“…Oxytocin also elicited a long-lasting nonselective cation current consistent with SRCE in late pregnant rat myometrium [60]. Furthermore, the sustained phase of [Ca 2+ ] i elevation after PGF2α-induced contractions in pregnant guinea pig myometrium was not affected by nifedipine [52], consistent with SRCE.…”
Section: Signal-regulated (Capacitative) Channels and Other Cation Chsupporting
confidence: 60%
“…In pregnant guinea pig myometrium, PGF2α stimulated sustained depolarization and biphasic increases in [Ca 2+ ] i at mid to late-pregnancy; nifedipine inhibited most of the former but only some of the latter [52]. Verapamil, an L-type channel inhibitor, significantly reduced PGF2α-stimulated PI turnover in late pregnant human myometrium [2,47].…”
Section: Proteins Responsible For Membrane Calcium Entry and Exit Patmentioning
confidence: 99%
“…Nifedipine produced a 13-mV depolarization in membrane potential and caused cessation of slow waves. This effect is similar to that reported previously in the guinea pig myometrium where nifedipine produced an identical 13-mV depolarization and abolished spontaneous electrical activity (8). In uterine muscles, depolarization caused by nifedipine was thought to be due to suppression of K v or K Ca channels.…”
Section: Discussionsupporting
confidence: 77%